(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2016)
In this paper, we prove the generalized Hyers-Ulam stability of a general k-quadratic Euler-Lagrange functional equation: for any fixed positive integerÂ in intuitionistic fuzzy normed spaces using a fixed point method.